2020
DOI: 10.1080/01621459.2020.1722676
|View full text |Cite
|
Sign up to set email alerts
|

Using Maximum Entry-Wise Deviation to Test the Goodness of Fit for Stochastic Block Models

Abstract: The stochastic block model is widely used for detecting community structures in network data. How to test the goodness-of-fit of the model is one of the fundamental problems and has gained growing interests in recent years. In this paper, we propose a novel goodness-of-fit test based on the maximum entry of the centered and re-scaled adjacency matrix for the stochastic block model. One noticeable advantage of the proposed test is that the number of communities can be allowed to grow linearly with the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…VOS Viewer, also called VV, is software used to visualize bibliometric maps (Barra & Zotti, 2017;Hu et al, 2020;Mundt & Mundt, 2020) or data sets containing bibliographic fields such as title, author, journal, and others. In the world of research, VV is used for bibliometric analysis, mapping topics for the latest research, finding the most widely used references in certain fields, and others.…”
Section: Vos Viewermentioning
confidence: 99%
“…VOS Viewer, also called VV, is software used to visualize bibliometric maps (Barra & Zotti, 2017;Hu et al, 2020;Mundt & Mundt, 2020) or data sets containing bibliographic fields such as title, author, journal, and others. In the world of research, VV is used for bibliometric analysis, mapping topics for the latest research, finding the most widely used references in certain fields, and others.…”
Section: Vos Viewermentioning
confidence: 99%
“…Besides estimating the block structure from a given observed data matrix based on an LBM, it is also important to test the validity of a model (i.e., the number of blocks) or an estimation result. Until now, several tests [3,14,22,35,37] have been proposed for determining the number of blocks in block models, such as a stochastic block model (SBM), which is a model for a square symmetric matrix (e.g., an adjacency matrix of the network structure). Among these studies, only [35]'s test can be applied to the LBM setting; however, its target is different from ours in that it is limited to the number of blocks, not to the cluster memberships.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to an SBM, several studies have proposed a statistical test for a given set of community memberships of an observed matrix [8,14,16]. In [8], based on the numbers of edges within and across the clusters, two tests were proposed for an SBM; one of these tests included a goodness-of-fit test of community memberships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical test on the number of biclusters K. Although there have been many studies for testing whether an observed matrix A contains any large average submatrix or not [6,7,10,32,35], few statistical test methods have been proposed for the number of biclusters K in matrix A. Recently, statistical tests on K has been proposed in [3,28,30,55] with the constraint that the underlying bicluster structure should be represented by a regular grid (as shown in Figure 1 (b-2)) 1 . However, if the latent bicluster structure does not satisfy the regular grid constraint (as shown in Figure 1 (b-1)), such a test needs larger hypothetical number of biclusters K 0 (i.e., finer bicluster structure) to accept the null hypothesis K = K 0 than necessary, which would not be desirable in the perspective of interpreting the accepted bicluster structure.…”
Section: Introductionmentioning
confidence: 99%